Self-Efficacy, Self-Awareness and Parental Involvement as Determinants of Goal Setting Among the Adolescent Youth - Makewa, Lazarus Ndiku; Ngila, Winnie Muthoni (IJRDO-Journal of Applied Science, 2015)
This study endeavored to test how self-efficacy, self-awareness and parental involvementaffected goal setting among the youth. The study was descriptive and comparative in designin that subjects were measured once and that the variables were compared between subjectsin terms of gender. Purposive sampling was done to obtain a sample with adolescents only;the sample consisted of 148 youths, making 31.092 % of respondents all aging between 13and 24 years. A questionnaire was constructed to test on self-efficacy, self-awareness andparental involvement as determinants of goal setting among the youth. The questionnaire hada reliability of 0.767. Mean ratings of the variables were compared in analysis of thedescriptive information of the variables. Results of frequencies and mean comparisons wereused to answer the first research question. ANOVA was done to determine whether there wasa significant difference in the determinants of goal setting among the youth in terms ofgender so as to answer the second question. To answer question three, Pearson correlationcoefficient was determined. The results indicate that respondents bear perceived self-efficacythat can influence them positively in goal setting. While self-efficacy and self-awarenessemanate from within an individual, parental involvement is an external factor. Nevertheless,among the three variables, it has the highest mean rating as a factor that influences goalsetting among the adolescent youths. The study established that there is no significantdifference in the determinants of goal setting between male and female youths. Anothermoderately positive relationship is observed between self-efficacy and parental involvementin goal setting among the youth.